Light Microscopy: methods and protocols - Markaki, Yolanda; Harz, Hartmann (Methods in molecular biology, 2017)
This volume addresses up-to-date light microscopy approaches and toolsets offered for live- or fixed-cell observations. The imaging strategies discussed in this book include confocal laser scanning and spinning disk confocal microscopy, FRET, FRAP, and laser microsurgery experiments. Chapters also describe the use of these imaging methodologies to study properties of a multitude of biomolecular targets in a broad range of model systems ranging from bacteria over tissue to whole animal imaging. Light Microscopy: Methods and Protocols puts special focus on system instrumentation parameters and sophisticated labeling and detection methods. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and thorough, Light Microscopy: Methods and Protocols offers the novice user with straightforward strategies to address biological questions, while providing the experienced researcher with the latest applications that can be useful in routine practices. This book also serves as a useful teaching manual in practical courses on light microscopy.
Keywords: Mikroskopie